2016
DOI: 10.1038/mi.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Donor interleukin-22 and host type I interferon signaling pathway participate in intestinal graft-versus-host disease via STAT1 activation and CXCL10

Abstract: Acute graft-versus-host disease (aGVHD) remains a major complication following allogeneic hematopoietic cell transplantation, limiting the success of this therapy. We previously reported that interleukin-22 (IL-22) participates to aGVHD development, but the underlying mechanisms of its contribution remain poorly understood. In this study, we analyzed the mechanism of the pathological function of IL-22 in intestinal aGVHD. Ex-vivo colon culture experiments indicated that IL-22 was able to induce Th1-like inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
4
27
1
2
Order By: Relevance
“…A recent supporting study from Hanash et al showed that IL-22 specifically signals through STAT3 in stem cells within the crypts of both the small and large intestines to promote barrier regeneration in a murine model of graft versus host disease(21). While IL-22 has been shown in other models to signal through other STATs or MAPK/ERK pathways(22, 23), we found epithelial cell STAT3 to be necessary for IL-22 mediated protection in our acute model of ethanol and burn injury.…”
Section: Discussioncontrasting
confidence: 74%
“…A recent supporting study from Hanash et al showed that IL-22 specifically signals through STAT3 in stem cells within the crypts of both the small and large intestines to promote barrier regeneration in a murine model of graft versus host disease(21). While IL-22 has been shown in other models to signal through other STATs or MAPK/ERK pathways(22, 23), we found epithelial cell STAT3 to be necessary for IL-22 mediated protection in our acute model of ethanol and burn injury.…”
Section: Discussioncontrasting
confidence: 74%
“…Similarly, IL-17-producing Th17 cells have been shown to promote aGVHD; however, absence of IL-17 has been shown to promote aGVHD by augmenting Th1 responses (6,7,10,51,60,61). Despite the heterogeneous nature of the contribution of interferons to aGVHD disease progression, there is consensus that inhibition of STAT1, the mediator of biological activity of interferons, can ameliorate aGVHD (59,(62)(63)(64). Our results show that inhibition of PRMT5 potently reduces IFN-γ and IL-17 production by activated alloreactive T cells, accompanied by reduced STAT1 phosphorylation, culminating in a reduction in transcription of ISGs.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, IL-22 depletion or deficiency in the host was shown to increase aGvHD severity, and ILC3 and IL-22 were suggested to protect the intestinal stem cell pool and epithelial barrier function during inflammation (138). Interestingly, in another mouse model, donor-derived IL-22 was shown to have the opposite effect and contribute to the severity of GvHD by promoting Th1 cell infiltration in presence of IFN-α (139). …”
Section: Acute Gvhdmentioning
confidence: 99%